A kind of mullite whisker and preparation method thereof
By using silicon -rich materials for water and heat reactions and sintering, prepare a Mo Lai stone crystal beard with high length ratio, high purity and high toughness, solve the problem of high temperature and cost in the preparation process in the existing technology, and achieve low Industrial production of cost, low temperature.
Patent Information
- Application Number
- CN202311841908.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-28
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-12-28
Smart Images

Figure CN117802584B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of inorganic non-metallic materials, in particular to a method for preparing high aspect ratio mullite whiskers by using silicon-rich materials as raw materials. Background Art
[0002] Silicon-rich materials are a kind of chemical solid waste. The accumulated stock of silicon-rich materials in China has reached more than 3 million tons, and it increases by 100,000 to 200,000 tons each year. If silicon-rich materials are not properly disposed of, they will cause serious pollution to the environment. From the analysis of its chemical composition, silicon-rich materials contain a large amount of silicon dioxide, which can provide a silicon source for the preparation of mullite whiskers. Therefore, it is of great significance to carry out the recycling of silicon-rich materials with high added value.
[0003] Mullite whiskers (3Al2O3·2SiO2) are used in aerospace, military, electronic information and other high-tech fields. They have high melting point, low thermal expansion coefficient, strong chemical stability at high temperature, much higher strength than other chopped fibers, strong dispersibility, strong composite ability and compatibility with other materials, and large aspect ratio. They can improve the properties of reinforcement, toughness and high temperature resistance of various materials. They are a basic new material with outstanding performance and wide application, and are widely used in ceramics and ceramic-based composite materials.
[0004] At present, the research on mullite whiskers in China is mainly focused on the preparation and growth mechanism, and there is no mass-produced mullite whisker product that can be directly applied to material enhancement research. At present, there are mainly the following methods for preparing whiskers at home and abroad: Al2O3-SiO2 powder sintering method, sol-gel method, mineral decomposition method, etc., but most methods require a high temperature of more than 1200°C to prepare mullite whiskers, and high-purity, high aspect ratio, and easy-to-disperse whiskers have not yet been obtained. This is mainly due to the influence of factors such as the preparation method, whisker growth mechanism, whisker surface force and electrostatic effect. The prepared whiskers are prone to agglomeration, thereby affecting the toughening and reinforcement effect of the whisker material.
[0005] Therefore, how to provide a method for preparing mullite whiskers with simple preparation method, low cost and high aspect ratio is a problem that technicians in this field need to solve urgently. Summary of the invention
[0006] In view of this, the present invention provides a method for preparing high aspect ratio mullite whiskers using silicon-rich material as raw material, which has low raw material cost, low sintering temperature, simple operation, green and environmental protection, and can be mass-produced. The prepared mullite whiskers have high aspect ratio, high purity and high toughness.
[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0008] On the one hand, the present invention provides a method for preparing mullite whiskers, comprising the following steps:
[0009] (1) mixing a silicon-rich material, a silicon-aluminum ratio regulator, a regulator, and water, performing a hydrothermal reaction, standing and stratifying, and obtaining a slurry;
[0010] (2) drying the slurry and then crushing it to obtain powder;
[0011] (3) adding a catalyst, a rare earth oxide, carbon powder, and a surface adsorbent to the powder, mixing them evenly, sintering them, and cooling them to obtain a reaction product;
[0012] (4) washing the reaction product with water and drying it to obtain mullite whiskers.
[0013] Preferably, the mass ratio of the silicon-rich material, the silicon-aluminum ratio regulator, and the regulator in step (1) is (20-40): (40-60): (1-20).
[0014] Preferably, the temperature of the hydrothermal reaction is 120-180° C., and the reaction time is 1-3 h.
[0015] Preferably, the silicon-rich material in step (1) is a solid waste containing silicon dioxide. Further preferably, the silicon-rich material includes one or more of diatomaceous earth, clay, kaolin, feldspar, nepheline syenite, shale, zeolite, opal, mullite, andalusite, epidote, cordierite, titanite, almandine, beryl, blue stone, sillimanite, diopside, grossular garnet, olivine, volcanite, wollastonite, serpentine, talc, chrysocolla, tremolite, basalt, andesite, trachyte, rhyolite, citrine, kyanite, bauxite, montmorillonite, mica, illite, vermiculite, sepiolite, chlorite, alumina, obsidian, actinolite, pitch rock, perlite, pumice, silica-alumina, fly ash, and zeolite.
[0016] Preferably, the silicon-aluminum ratio regulator includes one or more of aluminum oxide, aluminum chloride, aluminum sulfate and aluminum hydroxide.
[0017] Preferably, the regulator is an organic acid and / or an inorganic acid. Further preferably, the regulator includes one or more of dilute hydrochloric acid, dilute sulfuric acid, dilute nitric acid, formic acid, acetic acid, oxalic acid, tartaric acid, hypochlorous acid, carbonic acid, citric acid, malic acid and hydrofluoric acid.
[0018] Preferably, the drying temperature in step (2) is 150-200° C., and the drying time is 8-12 h.
[0019] Preferably, the mass ratio of the catalyst, rare earth oxide, carbon powder and surface adsorbent in step (3) is (1-15): (0.1-5): (1-20): (1-5).
[0020] Preferably, the catalyst in step (3) is a fluoride; further preferably, the catalyst includes one or more of aluminum fluoride, ammonium fluoride, sodium fluoride, magnesium fluoride, calcium fluoride and cryolite.
[0021] Preferably, the surface adsorbent is any one or more of sodium dodecylbenzene sulfonate, polyacrylamide, polyvinyl pyrrolidone, alkyl glucoside, fatty acid glyceride, fatty acid sorbitan, and polysorbate.
[0022] Preferably, the rare earth oxide includes one or more of lanthanum oxide, cerium oxide, and praseodymium oxide.
[0023] Preferably, the sintering temperature in step (3) is 700-1100° C., the sintering holding time is 4-7 hours, and the rate of heating to the sintering temperature is 5-10° C. / min.
[0024] Preferably, the cooling in step (3) is performed by a step-by-step cooling method to cool to room temperature.
[0025] Further preferably, the step-by-step cooling method is: naturally cool down from 700-1100°C to 650-750°C, and keep warm for 50-70min; continue to naturally cool down from 650-750°C to 450-550°C, and keep warm for 50-70min; continue to naturally cool down from 450-550°C to 200-400°C, and keep warm for 50-70min; continue to naturally cool from 200-400°C to room temperature.
[0026] On the other hand, the present invention also provides a mullite whisker prepared by any of the above methods, wherein the mullite whisker has a length of 15-100 μm, a diameter of 100-300 nm, and a purity of more than 95%.
[0027] The present invention provides a method for preparing mullite whiskers, which has the following beneficial effects compared with the prior art:
[0028] The invention uses chemical solid waste silicon-rich materials as reaction raw materials, contains a large amount of silicon dioxide, has a theoretical basis for providing a silicon source for preparing mullite whiskers, is low in price, has abundant sources, improves waste utilization, reduces environmental pollution, is green and environmentally friendly, and has a low sintering process temperature and simple operation. The prepared mullite whiskers have a high aspect ratio, high purity and high toughness, and are suitable for industrial mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0030] Figure 1 The XRD spectrum of the mullite whisker obtained in Example 1;
[0031] Figure 2 This is a scanning electron microscope photograph of the mullite whisker obtained in Example 1;
[0032] Figure 3 This is a scanning electron microscope photo of the mullite whisker obtained in Example 2;
[0033] Figure 4 This is a scanning electron microscope photograph of the mullite whisker obtained in Example 3;
[0034] Figure 5 This is a scanning electron microscope photograph of the mullite whisker obtained in Example 4;
[0035] Figure 6 This is a scanning electron microscope photograph of the mullite whisker obtained in Example 5;
[0036] Figure 7 This is a scanning electron microscope photograph of the mullite whisker obtained in Comparative Example 1;
[0037] Figure 8 This is a scanning electron microscope photograph of the mullite whisker obtained in Comparative Example 2;
[0038] Fig. 9 This is a scanning electron microscope photograph of the mullite whisker obtained in Comparative Example 3;
[0039] Fig.10 This is a scanning electron microscope photograph of the mullite whisker obtained in Comparative Example 4;
[0040] Fig.11 This is an image diagram showing the effect of the amount of mullite whisker added on the compressive strength of toughened PU foam obtained in Example 1;
[0041] Fig.12 This is a scanning electron microscope photograph of the toughened PU foam obtained by adding 0.3% of the mullite whiskers obtained in Example 1;
[0042] Fig.13 This is a scanning electron microscope photo of PU foam without adding mullite whiskers. DETAILED DESCRIPTION
[0043] Embodiments of the present invention are described in detail below, and the examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals represent the same or similar elements or elements with the same or similar functions from beginning to end. The embodiments described below by reference to the accompanying drawings are exemplary, are only used to explain the present invention, and are not to be construed as limitations of the present invention. In the embodiments, if specific techniques or conditions are not indicated, the techniques or conditions described in the literature in this area or the product specifications are carried out. The reagents used or the instruments that are not indicated by the manufacturer are all conventional products that can be obtained commercially.
[0044] In one aspect of the present invention, the present invention provides a method for preparing mullite whiskers, comprising the following steps:
[0045] S100. Mix the silicon-rich material, silicon-aluminum ratio regulator, regulator and water, put them into a dispersed sand mill for stirring to prepare a mixed liquid, pour the mixed liquid into a hydrothermal reactor, place the hydrothermal reactor in an oven for hydrothermal reaction, let the liquid in the hydrothermal reactor stand for stratification after the reaction, pour out the upper layer of liquid to obtain a lower layer slurry.
[0046] In this step, the mass ratio of the silicon-rich material, the silicon-aluminum ratio regulator, and the regulator is (20-40): (40-60): (1-20), for example, 20:60:20, 25:65:10, 32:56:12, 40:59:1, etc., and the liquid-solid ratio is 1-10 ml / g. The ratio is adjusted according to the content of silicon and aluminum in different raw materials so that the ratio of alumina to silicon dioxide in the final mixed raw material reaches 3:2.
[0047] Further, the silicon-rich material in step (1) is a solid waste containing silicon dioxide. Further preferably, the silicon-rich material includes one or more of diatomaceous earth, clay, kaolin, feldspar, nepheline syenite, shale, zeolite, opal, mullite, andalusite, epidote, cordierite, titanite, almandine, beryl, blue stone, sillimanite, diopside, grossular garnet, olivine, volcanite, wollastonite, serpentine, talc, chrysocolla, tremolite, basalt, andesite, trachyte, rhyolite, citrine, kyanite, bauxite, montmorillonite, mica, illite, vermiculite, sepiolite, chlorite, alumina, obsidian, actinolite, pitch rock, perlite, pumice, silica-alumina, fly ash, and zeolite.
[0048] The invention uses chemical solid waste silicon-rich materials as reaction raw materials, contains a large amount of silicon dioxide, has a theoretical basis for providing a silicon source for preparing mullite whiskers, is low in price, has abundant sources, improves waste utilization, reduces environmental pollution, and is green and environmentally friendly.
[0049] Furthermore, the silicon-aluminum ratio regulator includes one or more of aluminum oxide, aluminum chloride, aluminum sulfate and aluminum hydroxide, which can be used to adjust the silicon content and aluminum content in the mullite whisker, thereby obtaining mullite whiskers with a high aspect ratio.
[0050] Further, the regulator is an organic acid and / or an inorganic acid. Preferably, the regulator includes one or more of dilute hydrochloric acid, dilute sulfuric acid, dilute nitric acid, formic acid, acetic acid, oxalic acid, tartaric acid, hypochlorous acid, carbonic acid, citric acid, malic acid and hydrofluoric acid. More preferably, the mass concentration of dilute hydrochloric acid is 10%, the mass concentration of dilute sulfuric acid is 20%, and the mass concentration of dilute nitric acid is 40%.
[0051] The present invention uses acid as a regulator, which can reduce the viscosity of the silicon-rich material, improve the dispersibility of the reaction raw materials, and make the reaction more complete.
[0052] Furthermore, the stirring speed is 3000-5000rpm, and the time is 30-60min; the temperature of the hydrothermal reaction is 120-180°C, for example, 120°C, 150°C, 180°C, etc., the reaction time is 1-3h, for example, 1h, 2h, 3h, etc., and the standing time is 20-120min, for example, 20min, 60min, 120min, etc., and there is no special limitation on this, and the obvious separation of solid and liquid is used as the observation basis.
[0053] The purpose of the hydrothermal reaction of the present invention is to remove alkaline oxide impurities. Adding a regulator to create an acidic environment can, firstly, inhibit the hydrolysis of silicon dioxide and ensure the stability of the silicon source; secondly, it can promote the hydrolysis of alkaline oxides in silicon-rich materials, combine with acid ions to form salts and water, dissolve in the upper liquid, and leave silicon dioxide and alumina slurry in the lower layer.
[0054] S200. Drying the slurry to obtain dry agglomerates, removing yellow hard matter on the surface of the dry agglomerates, and crushing the remaining white part to obtain powder.
[0055] In this step, the drying temperature is 150-200°C, for example, 150°C, 180°C, 200°C, etc., and the drying time is 8-12h, for example, 8h, 10h, 12h, etc. In the dry agglomerate obtained by drying the slurry in the present invention, the surface layer is the remaining stubborn salt complex, which is removed to obtain a high-purity mullite whisker reaction precursor.
[0056] S300. Put the powder into a corundum crucible, add a catalyst, a rare earth oxide, carbon powder, and a surface adsorbent into the powder and mix them evenly, put the corundum crucible into a box-type resistance furnace for sintering, and obtain a reaction product after cooling.
[0057] In this step, the mass ratio of the catalyst, rare earth oxide, carbon powder and surface adsorbent is (1-15):(0.1-5):(1-20):(1-5), for example, it can be 15:1:10:2, 1:5:1:1, 10:2:20:5, etc.
[0058] Furthermore, the catalyst is a fluoride; preferably, the catalyst includes one or more of aluminum fluoride, ammonium fluoride, sodium fluoride, magnesium fluoride, calcium fluoride and cryolite. The present invention uses fluoride as a catalyst to react at high temperature to generate hydrogen fluoride gas, catalyzes the nucleation growth of mullite whiskers in a hydrogen fluoride atmosphere, and reduces the temperature of mullite crystal nucleation.
[0059] Further, the surface adsorbent includes any one or more of sodium dodecylbenzenesulfonate polyacrylamide, polyvinyl pyrrolidone, alkyl glucoside, fatty acid glyceride, fatty acid sorbitan, and polysorbate, preferably sodium dodecylbenzenesulfonate. The adsorption of the above substances on the crystal surface as surface adsorbents occupies the growth site of the crystal and reduces the aspect ratio of the surface structure. In the nucleation process, the addition of surface adsorbents prevents ions from aggregating into small clusters, inhibits the formation of crystal nuclei, promotes crystal nuclei to aggregate and grow into coarse-grained mullite crystals, thereby stabilizing growth, reducing fracture, and obtaining whiskers with a high aspect ratio.
[0060] Furthermore, the rare earth oxide includes one or more of lanthanum oxide, cerium oxide, and praseodymium oxide, preferably lanthanum oxide La2O3. The addition of rare earth oxide reacts with silicon dioxide in the silicon-rich material at high temperature to generate silicates such as lanthanum silicate, which are distributed in a dendrite-like manner in the mullite crystal structure. The dendrites are toughened, the flexural strength is increased, and the toughness of the mullite whiskers is improved.
[0061] Further, the sintering temperature is 700-1100°C, for example, 700°C, 800°C, 1000°C, 1100°C, etc., the sintering holding time is 4-7h, for example, 4h, 5h, 6h, 7h, etc., and the rate of heating to the sintering temperature is 5-10°C / min, for example, 5°C / min, 8°C / min, 10°C / min, etc. The carbon powder is evenly dispersed in the reactants during the sintering reaction, and fully reacts with oxygen at 700-1100°C to generate a large amount of carbon dioxide gas, thereby generating a large number of pores and forming a porous structure, which provides space for the uniform growth of whiskers, is conducive to the growth of mullite crystals into long whiskers, and can also reduce whisker agglomeration and promote whisker dispersion.
[0062] Furthermore, the cooling adopts a step-by-step cooling method to cool to room temperature. Preferably, the step-by-step cooling method is: naturally cooling from 700-1100°C to 650-750°C, and keeping warm for 50-70min; continuing to naturally cool from 650-750°C to 450-550°C, and keeping warm for 50-70min; continuing to naturally cool from 450-550°C to 200-400°C, and keeping warm for 50-70min; continuing to naturally cool from 200-400°C to room temperature.
[0063] Compared with the traditional preparation method, the present invention does not adopt the method of cooling with the furnace, but adopts a step-by-step slow cooling method to reduce the supercooling, promote grain growth, and further promote the formation of mullite whiskers with a high aspect ratio; in addition, the present invention also reduces the step of using molten salt as a sintering aid, further reducing costs.
[0064] S400. The reaction product is washed with boiling water and dried at 120-150° C. to obtain high-purity and high-aspect-ratio mullite whiskers.
[0065] In this step, the reaction product is washed with boiling water and dried to further improve the purity of the mullite whiskers and to reduce impurities.
[0066] In another aspect of the present invention, the present invention provides a mullite whisker, which is prepared by the method described above. Therefore, the mullite whisker has all the characteristics and advantages of the method described above, which will not be repeated here. In general, the mullite whisker has a length of 15-100 μm, a diameter of 100-300 nm, and a purity of more than 95%.
[0067] The present invention will be described below by specific examples, and it will be appreciated by those skilled in the art that the following specific examples are only for illustrative purposes, and do not limit the scope of the present invention in any way. In addition, in the following examples, unless otherwise specified, the reagents and equipment used are all commercially available. If in the following examples, specific treatment conditions and treatment methods are not clearly described, then conditions and methods known in the art can be used to process.
[0068] Example 1
[0069] (1) After weighing 25.6% kaolin, 65.4% aluminum hydroxide, 9% citric acid, and deionized water (liquid-to-solid ratio 5 ml / g), the materials were placed in a dispersed sand mill and stirred at a speed of 3000 r / min for 60 min to prepare a mixed solution;
[0070] (2) pouring the mixed liquid into a hydrothermal reactor, placing the hydrothermal reactor in an oven for reaction, the reaction temperature is 180° C., the reaction time is 2 h, the liquid in the hydrothermal reactor after the reaction is allowed to stand for 1 h, the upper liquid is poured out, and the remaining slurry is dried at a drying temperature of 200° C. for 12 h to obtain a dry agglomerate, removing the yellow hard matter on the surface of the dry agglomerate, and crushing the remaining white part into powder;
[0071] (3) putting the powder into a corundum crucible, adding 15% aluminum fluoride, 1% rare earth oxide La2O3, 10% carbon powder, and 2% sodium dodecylbenzene sulfonate, putting them into the corundum crucible and mixing them evenly, putting the corundum crucible into a box-type resistance furnace for sintering, keeping the temperature at 900°C for 5 hours, cooling by step cooling method, keeping the temperature at 700°C for 1 hour, keeping the temperature at 500°C for 1 hour, and keeping the temperature at 300°C for 1 hour, and then cooling naturally to obtain a reaction product;
[0072] (4) The reaction product is washed with boiling water and dried under normal pressure to obtain mullite whiskers.
[0073] Example 2
[0074] (1) After weighing 32.1% of feldspar, 55.9% of aluminum oxide, 12% of formic acid, and deionized water (liquid-to-solid ratio 5 ml / g), the materials were placed in a dispersed sand mill and stirred at a speed of 3000 r / min for 50 min to prepare a mixed solution;
[0075] (2) pouring the mixed liquid into a hydrothermal reactor, placing the hydrothermal reactor in an oven for reaction, the reaction temperature is 180°C, the reaction time is 10 hours, the liquid in the hydrothermal reactor after the reaction is allowed to stand for 1 hour, pouring out the upper liquid, and drying the remaining slurry, the drying temperature is 200°C, the drying time is 12 hours, and a dry agglomerate is obtained, the yellow hard matter on the surface of the dry agglomerate is removed, and the remaining white part is crushed into powder;
[0076] (3) putting the powder into a corundum crucible, adding 15% aluminum fluoride, 1% rare earth oxide La2O3, 10% carbon powder, and 2% sodium dodecylbenzene sulfonate, putting them into the corundum crucible and mixing them evenly, putting the corundum crucible into a box-type resistance furnace for sintering, keeping the temperature at 800°C for 6 hours, cooling by step cooling method, keeping the temperature at 680°C for 50 minutes, keeping the temperature at 480°C for 70 minutes, and keeping the temperature at 350°C for 50 minutes, and then cooling naturally to obtain a reaction product;
[0077] (4) The reaction product is washed with boiling water and dried under normal pressure to obtain mullite whiskers.
[0078] Example 3
[0079] (1) Weigh 44.4% of cordierite, 51.2% of aluminum sulfate, 4.4% of dilute sulfuric acid (mass concentration 20%), and deionized water (liquid-to-solid ratio 5 ml / g), put them into a dispersed sand mill and stir them at a speed of 4000 r / min for 40 min to prepare a mixed solution;
[0080] (2) pouring the mixed liquid into a hydrothermal reactor, placing the hydrothermal reactor in an oven for reaction, the reaction temperature is 150° C., the reaction time is 2 h, the liquid in the hydrothermal reactor after the reaction is allowed to stand for 1 h, the upper liquid is poured out, and the remaining slurry is dried at a drying temperature of 200° C. for 8 h to obtain a dry agglomerate, removing the yellow hard matter on the surface of the dry agglomerate, and crushing the remaining white part into powder;
[0081] (3) putting the powder into a corundum crucible, adding 1% aluminum fluoride, 5% rare earth oxide La2O3, 1% carbon powder, and 1% sodium dodecylbenzene sulfonate, putting them into the corundum crucible and mixing them evenly, putting the corundum crucible into a box-type resistance furnace for sintering, keeping the temperature at 700°C for 7h, cooling by step cooling method, keeping the temperature at 650°C for 70min, keeping the temperature at 450°C for 1h, and keeping the temperature at 200°C for 1h, and then cooling naturally to obtain a reaction product;
[0082] (4) The reaction product is washed with boiling water and dried under normal pressure to obtain mullite whiskers.
[0083] Example 4
[0084] (1) 25.6% of silicon-aluminum waste (silicon-aluminum ratio of 6.6:0.17), 65.4% of aluminum hydroxide, 9% of dilute hydrochloric acid (mass concentration of 10%), and deionized water (liquid-to-solid ratio of 5 ml / g) were weighed and placed in a dispersed sand mill for stirring at a speed of 4000 r / min for 60 min to prepare a mixed solution; the chemical composition of the silicon-aluminum waste is shown in Table 1:
[0085] Table 1
[0086] Raw material ingredients <![CDATA[SiO2]]> <![CDATA[Na2O]]> <![CDATA[SO3]]> CaO MgO <![CDATA[Al2O3]]> content(%) 66.1 17.5 8.7 3.2 2.8 1.7
[0087] (2) pouring the mixed liquid into a hydrothermal reactor, placing the hydrothermal reactor in an oven for reaction, the reaction temperature is 180° C., the reaction time is 1 h, the liquid in the hydrothermal reactor after the reaction is allowed to stand for 1 h, the upper liquid is poured out, and the remaining slurry is dried at a drying temperature of 200° C. for 10 h to obtain a dry agglomerate, removing the yellow hard matter on the surface of the dry agglomerate, and crushing the remaining white part into powder;
[0088] (3) putting the powder into a corundum crucible, adding 10% sodium fluoride, 2% rare earth oxide La2O3, 20% carbon powder, and 5% sodium dodecylbenzene sulfonate, putting them into the corundum crucible and mixing them evenly, putting the corundum crucible into a box-type resistance furnace for sintering, keeping the temperature at 1000°C for 5 hours, cooling by a step-down method, keeping the temperature at 750°C for 1 hour, keeping the temperature at 550°C for 50 minutes, and keeping the temperature at 400°C for 70 minutes, and then cooling naturally to obtain a reaction product;
[0089] (4) The reaction product is washed with boiling water and dried under normal pressure to obtain mullite whiskers.
[0090] Example 5
[0091] (1) After weighing 70.4% fly ash, 17.6% aluminum oxide, 12% acetic acid, and deionized water (liquid-to-solid ratio 5 ml / g), the materials were placed in a dispersed sand mill and stirred at a speed of 5000 r / min for 30 min to prepare a mixed solution; the chemical composition of the fly ash is shown in Table 2:
[0092] Table 2
[0093] Raw material ingredients <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[TiO2]]> CaO <![CDATA[Fe2O3]]> <![CDATA[K2O]]> Other trace oxides content(%) 40.25 49.61 1.98 2.97 1.36 1.7 2.13
[0094] (2) pouring the mixed liquid into a hydrothermal reactor, placing the hydrothermal reactor in an oven for reaction, the reaction temperature is 120° C., the reaction time is 3 h, the liquid in the hydrothermal reactor after the reaction is allowed to stand for 1 h, the upper layer of liquid is poured out, and the remaining slurry is dried at a drying temperature of 150° C. for 12 h to obtain a dry agglomerate, removing the yellow hard matter on the surface of the dry agglomerate, and crushing the remaining white part into powder;
[0095] (3) putting the powder into a corundum crucible, adding 15% ammonium fluoride, 1% rare earth oxide La2O3, 10% carbon powder, and 2% sodium dodecylbenzene sulfonate, putting them into the corundum crucible and mixing them evenly, putting the corundum crucible into a box-type resistance furnace for sintering, keeping the temperature at 1100°C for 4 hours, cooling by step cooling method, keeping the temperature at 750°C for 50 minutes, keeping the temperature at 520°C for 1 hour, and keeping the temperature at 400°C for 1 hour, and then cooling naturally to obtain a reaction product;
[0096] (4) The reaction product is washed with boiling water and dried under normal pressure to obtain mullite whiskers.
[0097] Comparative Example 1
[0098] Comparative Example 1 is substantially the same as Example 1, except that no citric acid as a regulator is added.
[0099] Comparative Example 2
[0100] Comparative Example 2 is substantially the same as Example 1, except that no carbon powder is added.
[0101] Comparative Example 3
[0102] Comparative Example 3 is substantially the same as Example 1, except that sodium dodecylbenzene sulfonate, a surface adsorbent, is not added.
[0103] Comparative Example 4
[0104] Comparative Example 4 is substantially the same as Example 1, except that no rare earth oxide is added.
[0105] Comparative Example 5
[0106] Comparative Example 5 is substantially the same as Example 1, except that the catalyst is tin oxide.
[0107] Comparative Example 6
[0108] Comparative Example 6 is substantially the same as Example 1, except that the sintering process is as follows: keeping the temperature at 900° C. for 5 h, and naturally cooling to obtain the reaction product.
[0109] Comparative Example 7
[0110] Comparative Example 7 is substantially the same as Example 1, except that the sintering process is as follows: keeping at 900° C. for 5 h, cooling by step cooling method, keeping at 500° C. for 1 h, keeping at 300° C. for 1 h, and then naturally cooling to obtain the reaction product.
[0111] Comparative Example 8
[0112] Comparative Example 8 is substantially the same as Example 1, except that the remaining slurry is not dried in step (2).
[0113] Comparative Example 9
[0114] Comparative Example 9 is substantially the same as Example 1, except that step (4) is omitted, i.e., the reaction product is not washed with boiling water or dried.
[0115] The mullite whiskers of Examples 1-5 and Comparative Examples 1-9 were tested for their morphology, length, diameter, toughness, etc. The results are shown in Tables 3 and Figure 1-13 The toughness of mullite whiskers is represented by the compressive strength of toughened PU foam. The compressive strength of mullite whiskers toughened PU foam is determined by compression test. The experimental method is as follows:
[0116] The polyurethane degradation material, the catalyst N,N-dimethylethanolamine, the blowing agent fluorodichloroethane and the mullite whiskers obtained in Examples 1-5 and Comparative Examples 1-9 (wherein the added amount is the percentage of the added amount of mullite whiskers to the total mass) are uniformly mixed under high-speed stirring, the mixed sol is placed in a square mold, and PU foam is foamed at 25° C. to obtain toughened PU foam.
[0117] Table 3
[0118]
[0119]
[0120] Depend on Figure 1 It can be seen that the mullite whiskers prepared in Examples 1-5 of the present invention have significant mullite crystal peaks and lanthanum oxide crystal peaks, which proves that lanthanum oxide and mullite whiskers are compositely toughened, have no impurity peaks, and are high-purity mullite whiskers;
[0121] Depend on Figure 2-6 It can be seen that the mullite whiskers obtained in the embodiment of the present invention are needle-shaped whiskers with a whisker length of 15-100 μm, a diameter of 100-300 nm, a regular shape, and a slightly different degree of dispersion of the obtained whiskers;
[0122] Depend on Figure 7 It can be seen that the mullite whiskers without the addition of the regulator have more complex salt impurities, the whiskers are seriously agglomerated, and the morphology is poor;
[0123] Depend on Figure 8 It can be seen that the mullite whiskers without carbon powder are short in length and obviously agglomerated;
[0124] Depend on Fig. 9 It can be seen that the mullite whiskers without surface adsorbent are shorter in length, with some whisker breakage and agglomeration.
[0125] Depend on Fig.10 It can be seen that the mullite whiskers without the addition of rare earth oxides have more fracture phenomena.
[0126] Fig.11 It can be seen that with the increase of the amount of whiskers added, the compressive strength of the PU foam first increases and then decreases. When the amount of whiskers added is 0.3%, the compressive strength of the toughened PU foam prepared reaches the maximum, which is about 0.35MPa. The reason is that adding whiskers can increase the support strength of the PU foam pore wall to a certain extent, thereby enhancing the compressive strength. However, when the mullite whiskers are added in excess, the whiskers will agglomerate, affecting the foaming reaction and causing an uneven pore structure. At this time, the support performance of the foam pore wall is reduced, resulting in a decrease in compressive strength. Experiments have shown that when 0.1-0.5% of the mullite whiskers obtained by the present invention are added, the compressive strength of the PU foam can be maximized, and the toughening effect is significant.
[0127] Depend on Fig.12It can be seen that after adding mullite whiskers, the collapse of PU foam is significantly reduced, the pores are full, the volume is moderate and large, the skeleton is relatively strong, the whiskers are evenly dispersed in the PU foam, the surface of the toughened PU foam is fine, and the compatibility is good, ensuring that the whiskers play a role in strengthening the skeleton in the PU foam matrix.
[0128] Depend on Fig.13 It can be seen that when mullite whiskers are not added, the prepared PU foam is not strong enough and has low support strength, which ultimately leads to small foam pores and more collapse.
[0129] In the description of this specification, the description with reference to the terms "one embodiment", "another embodiment", "yet another embodiment", "some embodiments", "some specific embodiments", "some other specific embodiments" and the like means that the specific features, structures, materials or characteristics described in conjunction with the embodiment are included in at least one embodiment of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in a suitable manner in any one or more embodiments or examples. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples, unless they are contradictory. In addition, it should be noted that in this specification, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated.
[0130] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing mullite whiskers, characterized in that: The following steps are involved: (1) mixing a silicon-rich material, a silicon-aluminum ratio regulator, a regulator, and water, performing a hydrothermal reaction, and standing to separate into layers to obtain a slurry; wherein the silicon-rich material is a solid waste containing silicon dioxide, the silicon-aluminum ratio regulator comprises one or more of aluminum oxide, aluminum chloride, aluminum sulfate, and aluminum hydroxide, and the regulator is an organic acid and / or an inorganic acid; (2) drying the slurry and then crushing it to obtain powder; (3) adding a catalyst, rare earth oxide, carbon powder and a surface adsorbent to the powder, mixing them evenly, sintering them and cooling them to obtain a reaction product; wherein the catalyst is a fluoride, and the surface adsorbent is any one or more of sodium dodecylbenzene sulfonate, polyacrylamide, polyvinyl pyrrolidone, alkyl glucoside, fatty acid glyceride, fatty acid sorbitan and polysorbate; (4) washing the reaction product with boiling water and drying it to obtain mullite whiskers; The cooling in step (3) is as follows: naturally cool down from 700-1100°C to 650-750°C, and keep warm for 50-70min; continue to naturally cool down from 650-750°C to 450-550°C, and keep warm for 50-70min; continue to naturally cool down from 450-550°C to 200-400°C, and keep warm for 50-70min; continue to naturally cool from 200-400°C to room temperature.
2. The method for preparing mullite whisker according to claim 1, wherein The mass ratio of the silicon-rich material, the silicon-aluminum ratio regulator, and the regulator in step (1) is (20-40): (40-60): (1-20); The temperature of the hydrothermal reaction is 120-180° C., and the reaction time is 1-3 hours.
3. The preparation method of mullite whisker according to claim 1 or 2, characterized in that, In step (1), the solid waste containing silicon dioxide includes one or more of diatomite, clay, kaolin, feldspar, nepheline syenite, shale, zeolite, opal, mullite, andalusite, epidote, cordierite, titanite, almandine, beryl, blue stone, sillimanite, diopside, grossular garnet, olivine, volcanite, wollastonite, serpentine, talc, chrysocolla, tremolite, basalt, andesite, trachyte, rhyolite, citrine, kyanite, bauxite, montmorillonite, mica, illite, vermiculite, sepiolite, chlorite, alumina, obsidian, actinolite, pitch rock, perlite, pumice, silica-alumina, fly ash, and zeolite; The regulator includes one or more of dilute hydrochloric acid, dilute sulfuric acid, dilute nitric acid, formic acid, acetic acid, oxalic acid, tartaric acid, hypochlorous acid, carbonic acid, citric acid, malic acid and hydrofluoric acid.
4. The method for preparing mullite whisker according to claim 1, wherein The drying temperature in step (2) is 150-200°C and the drying time is 8-12h.
5. The method for preparing mullite whiskers according to claim 1, wherein The mass ratio of the catalyst, rare earth oxide, carbon powder and surface adsorbent in step (3) is (1-15): (0.1-5): (1-20): (1-5).
6. The method for preparing mullite whiskers according to claim 1 or 5, wherein: The catalyst in step (3) includes one or more of aluminum fluoride, ammonium fluoride, sodium fluoride, magnesium fluoride, calcium fluoride and cryolite.
7. The method for preparing mullite whiskers according to claim 1, wherein In step (3), the sintering temperature is 700-1100°C, the sintering holding time is 4-7h, and the rate of heating to the sintering temperature is 5-10°C / min.
8. A mullite whisker prepared by the method according to any one of claims 1 to 7, characterized in that: The mullite whisker has a length of 15-100 μm, a diameter of 100-300 nm, and a purity of more than 95%.
Citation Information
Patent Citations
Method for synthesizing mullite whisker toughened corundum-mullite in situ
CN102086125A
Preparation method of sodium calcium silicate glass bottles
CN108117267A